Application of 18F-FDG PET/CT imaging in gallbladder inflammatory pseudotumor with elevated CA199: a case report and review of literature - Shao, Mingyan; Xu, Rong; Qi, Wanling; Luo, Zhehuang; Liao, Fengxiang; Fan, Sisi (Frontiers in Oncology, 2023)
Background:Gallbladder inflammatory pseudotumor(GIPT)is a nonspecific chronic proliferative inflammation of the gallbladder.At present, the pathogenesis is not clear, which may be related to bacterial and viral infections, congenital diseases, gallstones, chronic cholangitis and so on.GIPT is rare and the imaging examination has no obvious specificity. There are few reports on the 18F-FDG PET/CT imaging characteristics of GIPT. In this paper, 18F-FDG PET/CT findings of GIPT with elevated CA199 are reported and the literature is reviewed. Case description:A 69-year-old female patient presented with recurrent intermittent right upper abdominal pain for more than 1 year, followed by nausea and vomiting for 3 hours, without fever, dizziness, chest tightness and other symptoms.Complete CT, MRI, PET/CT and related laboratory tests, CEA (-), AFP (-), Ca199 224.50U/mL ↑,18F-FDG PET/CT images showed uneven thickening at the bottom of the gallbladder, slightly increased gallbladder volume, eccentric and localized thickening of the gallbladder body wall, nodular soft tissue density shadow, clear boundary, smooth gallbladder wall, presence and smooth hepatobiliary interface, increased FDG radioactivity uptake, SUVmax was 10.2.The tumor was resected after operation and was diagnosed as gallbladder inflammatory pseudotumor by postoperative pathology. Conclusion:Routine imaging of GIPT was not specific, and 18F-FDG PET/CT imaging was not specific for GIPT.In patients with chronic cholecystitis, when the CA199 increases, the gallbladder wall appears localized thickening, the hepatobiliary interface exists and is smooth, and the 18F-FDG metabolism is mildly to moderately increased. Gallbladder cancer cannot be diagnosed alone, and the possibility of gallbladder inflammatory pseudotumor should also be considered.However, it should be noted that the cases with unclear diagnosis should still be actively treated with surgery, so as not to delay the treatment opportunity.